2021
DOI: 10.1038/s41419-021-03579-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of PKM2 nuclear translocation in the constant activation of the NF-κB signaling pathway in cancer-associated fibroblasts

Abstract: Cancer-associated fibroblasts (CAFs) play critical roles in cancer progression by regulating tumor cell proliferation, angiogenesis, and metastasis. Recent studies demonstrated that CAFs induce inhibitory immune cell infiltration and chemotherapy resistance in gastric cancer by activating the NF-κB signaling pathway to secrete IL6, IL8, and other inflammatory factors. Inhibition of the NF-κB signaling pathway in CAFs might be a potential therapeutic strategy in gastric cancer. However, how the NF-κB pathway is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“… 41 Finally, nuclear PKM2 is required for the expression of cMYC 42 and NF-κB P65 nuclear retention, contributing to abnormal energy metabolism and continuous activation of inflammatory signaling pathways. 43 In support of this model pinpointing PARP1 and PKM2 as integral pieces of a self-perpetuating metabolic-inflammatory vicious circle of tissue damage, we found that blocking PARP1 activity or nuclear PKM2 translocation reduces PARP1 and PKM2 abundance in cells and tissues. Accordingly, the beneficial effects of PARP1 inhibition on RV function in PAB animals were largely recapitulated by PKM2 cytosolic activation.…”
Section: Discussionsupporting
confidence: 73%
“… 41 Finally, nuclear PKM2 is required for the expression of cMYC 42 and NF-κB P65 nuclear retention, contributing to abnormal energy metabolism and continuous activation of inflammatory signaling pathways. 43 In support of this model pinpointing PARP1 and PKM2 as integral pieces of a self-perpetuating metabolic-inflammatory vicious circle of tissue damage, we found that blocking PARP1 activity or nuclear PKM2 translocation reduces PARP1 and PKM2 abundance in cells and tissues. Accordingly, the beneficial effects of PARP1 inhibition on RV function in PAB animals were largely recapitulated by PKM2 cytosolic activation.…”
Section: Discussionsupporting
confidence: 73%
“…Second, PKM2 has been linked to apoptosis resistance via its ability to phosphorylate and stabilize pro-survival BCL-2 family proteins ( 51 , 52 ). PKM2 also translocates into the nucleus to modulate NF-κB-dependent gene expression and may inhibit caspase-3 indirectly via effects on miR-143 ( 51 , 53 ). Our published data show that mitochondrial integrity is significantly prolonged by LVS infection, and in keeping with this, BAX mRNA and protein are diminished and BAX translocation to mitochondria is significantly delayed ( 22 , 24 ), but whether this is attributable to HK2-VDAC interactions at mitochondrial surfaces and/or phosphoinositide 3-kinase signaling remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that melanoma cell–derived sEVs upregulated CXCL1 expression in CAFs through the IKK/IκB/NF‐κB signaling pathway, and blocking the IKK/IκB/NF‐κB signaling pathway remarkably attenuated the proangiogenic capability of CAFs. Previous studies had found that tumor cell–derived EVs could transfer M2 pyruvate kinase, latent membrane protein 1, and integrin beta‐like 1 into CAFs, leading to the persistent activation of the NF‐κB signaling pathway in CAFs 20‐23 . However, the mechanisms underlying NF‐κB signaling activation in CAFs induced by melanoma‐derived sEVs remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had found that tumor cell–derived EVs could transfer M2 pyruvate kinase, latent membrane protein 1, and integrin beta‐like 1 into CAFs, leading to the persistent activation of the NF‐κB signaling pathway in CAFs. 20 , 21 , 22 , 23 However, the mechanisms underlying NF‐κB signaling activation in CAFs induced by melanoma‐derived sEVs remained unclear. In this study, we discovered that hypoxia could promote the enrichment of the HSP90/p‐IKKα/β complex in melanoma‐derived sEVs.…”
Section: Discussionmentioning
confidence: 99%